Efficacy of gel immersion endoscopic ultrasonography for delineating the duodenal papilla and pancreatobiliary ducts: A retrospective study with video. Issue 1 (4th August 2022) - Toyonaga, Haruka; Kin, Toshifumi; Iwano, Kosuke; Nakamura, Risa; Shimizu, Takao; Chikugo, Koki; Ishii, Tatsuya; Nasuno, Hiroshi; Hayashi, Tsuyoshi; Takahashi, Kuniyuki; Yamazaki, Hajime; Katanuma, Akio
Abstract: Objectives: Endoscopic ultrasonography is an important examination for periampullary diseases. The duodenum is filled with water to ensure a clear image and distend the duodenal wall without burying the papilla within duodenal folds; however, peristalsis frequently makes it difficult to maintain water within the duodenum. The gel immersion method (intestine is filled with viscosity gel) has recently been attracting attention. We evaluated the usefulness of using this method for endoscopic ultrasonography to detect and delineate the major duodenal papilla. Methods: Fifty‐nine consecutive patients who underwent gel immersion‐endoscopic ultrasonography between February and March 2021 were included retrospectively. The papilla was observed by filling the duodenum with clear viscosity gel. Outcomes were the rate of duodenal distention, delineation rates of the papilla, the time required for delineation, volume of the gel used, and adverse events. Results: Duodenal distention was excellent, good, and poor in 58%, 34%, and 7% of cases, respectively. The delineation rates of the papilla in the axial and longitudinal views were 98% and 66%, respectively. The median time required to delineate the papilla in each view was 3.1 (range, 1.0–1.4) and 7.9 (1.9–28.6) min; the median volume of the gel used was 80 (30–150) ml and 100 (50–200) ml, respectively. No adverse events were noted. Conclusions: Gel immersion‐endoscopic ultrasonography provided sufficient duodenal distention, leading to high rates of detection and delineation of the papilla using a small volume of gel within a short time. This method may be useful for the evaluation of the ampullary region.